2017
DOI: 10.1007/s11356-017-9648-3
|View full text |Cite
|
Sign up to set email alerts
|

Generation of domestic waste electrical and electronic equipment on Fernando de Noronha Island: qualitative and quantitative aspects

Abstract: The accelerated growth trajectory of waste electrical and electronic equipment (WEEE) is a matter of concern for governments worldwide. In developing countries, the problem is more complex because municipal waste management is still a challenge for municipalities. Fernando de Noronha Island, an environmentally protected area, has a transfer station for solid waste before it is sent to the final destination abroad, which is different waste management model to most urban areas. In order to check the specifics of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Echegaray (2016) and Li et al (2012) showed variable ownership levels for different appliances, with MPs having the highest per-capita consumption and, DCs the lowest. Similarly, Araujo et al (2017) observed that mobile phone ownership was higher than other LE such as WMs, ACs, and SE such as tablets and DCs. In India, Borthakur and Govind (2019) that the number of the out-of-use mobile phone was equal to or higher than the number of in-use mobile phones.…”
Section: Factors-related To Purchase Decisionmentioning
confidence: 85%
See 1 more Smart Citation
“…Echegaray (2016) and Li et al (2012) showed variable ownership levels for different appliances, with MPs having the highest per-capita consumption and, DCs the lowest. Similarly, Araujo et al (2017) observed that mobile phone ownership was higher than other LE such as WMs, ACs, and SE such as tablets and DCs. In India, Borthakur and Govind (2019) that the number of the out-of-use mobile phone was equal to or higher than the number of in-use mobile phones.…”
Section: Factors-related To Purchase Decisionmentioning
confidence: 85%
“…Other notable methods of e-waste disposal include -"throwing e-waste with household solid waste/mixed waste" (Arain et al, 2020, Araujo et al, 2017, Blake et al, 2019, Borthakur and Govind, 2019, Bovea, M.D. et al, 2018, Chi et al, 2014, Fraige et al, 2012, Gök et al, 2017, Martinho et al, 2017, Pasiecznik et al, 2017, Rodrigues et al, 2020, Wieser and Tröger, 2018, "donate to others" (Abbondanza and Souza, 2019, Araujo et al, 2017, Borthakur and Govind, 2019, Cao et al, 2016, Colesca et al, 2014, Echegaray, 2016, Fraige et al, 2012, Hamdan and Saidan, 2020, Martinho et al, 2017, Rodrigues et al, 2020, "drop it to council collection centers/recycling centers" (Araujo et al, 2017, Borthakur and Govind, 2019, Chi et al, 2014, Fraige et al, 2012, Martinho et al, 2017, Rodrigues et al, 2020, Wieser and Tröger, 2018, "selling" (Cai et al, 2020, Cao et al, 2016, Chi et al, 2014, Echegaray, 2016, Fraige et al, 2012, Hamdan and Saidan, 2020, Nguyen et al, 2009, Ongondo and Williams, 2011, Ravindra and Mor, 2019…”
Section: Mode Of Disposalmentioning
confidence: 99%
“…Our review of articles retrieved from the Web of Science, and regulatory policies primarily in China, but extended to other countries informed our selection of 13 WEEE for this research (Andrae and Andersenl, 2010;Bae, 2016;Barba-Gutierrez et al, 2008;Chen et al, 2018;Chung et al, 2011;Control, 2004;Cucchiella et al, 2015;Dhiego Raphael Rodrigues Araujo et al, 2017;Kumar et al, 2019;Li et al, 2008;Lim et al, 2013;Matsuto et al, 2004;Minxi Wang, 2018;Oguchi et al, 2011Oguchi et al, , 2013Puneet et al, 2005;Renteria et al, 2011;Song et al, 2015;Taghipour et al, 2014;Tunsu et al, 2014;Yamasue et al, 2009;Zamprogno Rebello et al, 2020;Zeng et al, 2016). We included Incandescent Bulb (IB), Compact Fluorescent Lighting (CFL), Light Emitting Diode (LED) Bulb, Mobile Phone (MP), Desktop Computer (DC), Laptop Computer (LC), Liquid Crystal Display (LCD) Monitor, CRT TV, Plasma Display Panel (PDP) TV, LCD TV, Washing Machine (WM), Refrigerator (RF), Air Conditioner (AC).…”
Section: Metal Contents For Weee and Components By Collectionmentioning
confidence: 99%
“…Currently, a have a look at via way of means of the United Nations University (UNU) presents the biggest worldwide e-waste inventory, with a latest record posted in 2017 [14]. By rating the pinnacle thirty international locations round the sector via way of means of e-waste era, the information confirmed that China, the United States, and Japan had been the pinnacle international locations that generated huge portions of e-waste.…”
Section: Research Motivationmentioning
confidence: 99%